Synthesis and Determination of the Stability Constant of Mixed Ligand Complex of Y(III) - Cam, T.; Irez, G. (Asian Journal of Chemistry, 2014)
In this study, the stability constants of a mixed ligand complex of the yttrium ion by using ethylenediaminetetraacetic acid (EDTA, H2A) as a primary ligand and 2,3-dihydroxy benzoic acid (2,3-DHBA, H3B) as a secondary ligand has been investigated. The stability constants of the binary and mixed ligand complexes have been determined by using a potentiometric method and the BEST computer program at 25 ºC in a 0.1 M NaCl ionic medium. In addition, the identified complex by potentiometry was isolated as solids and the structural characteristics have been examined using IR, NMR, elemental analysis, AAS, ICP-OES, differential thermal analysis, thermogravimetric analysis and the conductivity method.